Desenvolvimento de um projeto de alarme para incêndio numa universidade pública - Brito Júnior, José Dionizio Crisostomo de (Universidade Federal Rural do Semi-Árido, 2020)
The objective of the study is to develop a fire alarm system for an academic complex of a public university regarding NBR 17240/2010, to qualify the evaluation process and the dimensioning of all components that involve a manual alarm system of fire alarm. fire. The research methodology has a real application, describing the step by step of creating the project, considering the quality and not the quantity, since the hypothesis of a poorly sized project is harmful. In addition, the methodology was based on procedures already determined in the literature, Brazilian standards and documents. It is based on a case study. In installations that do not have a fire alarm system, there is an increasing delay in fighting flames, firing the fire brigade, firing the fire brigade and emptying the building's public, therefore, the application of the adequacy recommendations the technical aspects of NBR 17,240 and the technical instruction of the military fire brigade of the state of Rio Grande do Norte No. 19/2018 is of paramount importance to solve the problem of how to alert everyone in a timely manner, within the proposed problem situation. In the end, it is concluded that the objectives are met and the question remains answered with the probability of the hypothesis, indicating that it is necessary to adopt parameters and guidelines in the standards, in order to develop a satisfactory fire alarm project for its real goal.
Keywords: Norma brasileira; Gestão de segurança; Medidas de proteção; Proteção Passiva; Incêndio; Brazilian standard; Security management; Protective measures; Passive protection; Fire; CIENCIAS EXATAS E DA TERRA::CIENCIA E TECNOLOGIA